Isolation And Development Of A Bacterial Consortium For The Potential Bioremediation Of Soil Contaminated With Used Lubricating Oil - Mohamed Razalli, Nurfarah Aina (2020)
Recently, there has been an uprising issue regarding the mismanagement of waste oil material which has been contaminating the environment. Reports on illegal discharge of waste hydrocarbon oil into rivers, oceans and crop soils are among the examples for this current predicament. Hence, this research endeavoured to develop a hydrocarbon degrading bacterial consortium isolated from a heavily polluted environment to remediate hydrocarbon compounds using used lubricating oil (ULO) as a model of contaminant. The work was initiated with isolation of microbial consortia from four different locations that are known to be contaminated area around Penang, Malaysia